AN ANALYSIS OF HYPERBOLE IN THE SOUR ALBUM OF OLIVIA RODRIGO - pande putu intan sruti prapila maha wirta putri; Mela Tustiawati Ida Ayu (SPHOTA: Jurnal Linguistik dan Sastra, 2022)
Abstract Figurative language has an important role in literary works. One of them is song lyric. Many songwriters write their songs using figures of speech for the deep message they want to convey to their target. Therefore, the aim of this study is to find out how many figures of speech hyperbole are contained in the lyrics of Olivia Rodrigo's song on the album "Sour". The researcher also tried to analyze the meaning of the sentences contained in the hyperbole figure of speech. The data studied were analyzed qualitatively to see the types and meanings contained in the song. The researchers found 13 data contained in the hyperbole figure of speech in the album "Sour" by Olivia Rodrigo. Hopefully this research is useful and also provides benefits for everyone to understand more about figurative language contained in song lyrics, because song lyrics are one of the literary works that contain a lot of figurative language. In addition, this research is expected to be able to contribute as a medium for language styles learning because songs are loved by many people so that teaching will be interesting   Abstrak Bahasa kiasan memiliki peranan penting dalam karya sastra. Salah satunya adalah lagu, banyak pencipta lagu menulis lagu mereka menggunakan majas untuk pesan mendalam yang ingin mereka sampaikan kepada target mereka. Oleh karena itu penelitian ini bertujuan untuk mengetahui berapa banyak majas hiperbola yang terdapat dalam lirik lagu Olivia Rodrigo pada album “Sour”. Peneliti juga mencoba menganalisis makna kalimat-kalimat yang terdapat dalam majas hiperbola. Data yang diteliti dianalisis secara kualitatif untuk melihat jenis dan makna yang terkandung dalam lagu tersebut. Peneliti menemukan 13 data yang terkandung majas hiperbola didalam album "Sour" oleh Olivia Rodrigo Semoga penelitian ini bermanfaat dan juga memberikan manfaat bagi semua orang untuk lebih memahami tentang bahasa kiasan yang terdapat dalam lirik lagu, karena lirik lagu merupakan salah satu karya sastra yang banyak mengandung bahasa kiasan. Selain itu, penelitian ini diharapkan mampu berkontribusi sebagai media untuk pembelajaran gaya bahasa karena lagu digemari banyak orang sehingga pengajaran akan menarik.